1989
DOI: 10.1182/blood.v73.1.90.bloodjournal73190
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo metabolism of recombinant human erythropoietin in the rat

Abstract: We compared the in vivo plasma clearance and organ accumulation in anesthetized rats of 125I-labeled, recombinant human erythropoietin and 125I-labeled, desialylated recombinant erythropoietin. The immediate volume of distribution of 125I-labeled, recombinant erythropoietin approximated that of the plasma volume. Its plasma clearance was multiexponential, with an initial rapid distribution phase (t1/2 = 53 minutes) and a slower elimination phase (t1/2 = 180 minutes). Organ accumulation of labeled recombinant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 24 publications
1
22
0
1
Order By: Relevance
“…Of major importance are the terminal sialic acid residues of these glycans (69). Like other asialo‐glycoproteins, asialo‐Epo is rapidly removed via galactose receptors of hepatocytes (70), because galactose is the preterminal sugar of the glycans. On the contrary, the introduction of additional N‐glycans into recombinant Epo by site‐directed mutagenesis results in a prolonged in vivo survival of the molecules (71, 72).…”
Section: Isolation and Chemical Characterisation Of Epomentioning
confidence: 99%
“…Of major importance are the terminal sialic acid residues of these glycans (69). Like other asialo‐glycoproteins, asialo‐Epo is rapidly removed via galactose receptors of hepatocytes (70), because galactose is the preterminal sugar of the glycans. On the contrary, the introduction of additional N‐glycans into recombinant Epo by site‐directed mutagenesis results in a prolonged in vivo survival of the molecules (71, 72).…”
Section: Isolation and Chemical Characterisation Of Epomentioning
confidence: 99%
“…Epo isoforms having reduced sialic acids have a shortened plasma half‐life (71). In the latter case, an increased number of the preterminal galactose residues of the Epo molecules are exposed, resulting in rapid hepatic clearance (72–74). To some extent, native Epo as well as rhEpo or NESP may be desialylated by action of tissue and blood sialidases followed by galactose receptor‐mediated uptake through hepatocytes.…”
Section: Metabolism Of Epomentioning
confidence: 99%
“…Information regarding the in vivo clearance of Epo remains incomplete. Some studies have shown that Epo is cleared by the liver (35,36) and the kidney (37) , however, their effects seem to be minimal (38). Receptor-mediated endocytosis in the bone marrow by erythroid progenitors followed by lysosomal degradation is the primary organ of Epo elimination from the body (17).…”
Section: Epo Pharmacokineticsmentioning
confidence: 99%
“…Identifying possible sources for the non-receptor mediated clearance mechanism of Epo is important for future characterization of the pathway. Some studies have shown that Epo is cleared by the liver (35,36) and the kidney (37) , however, their effects seem to be minimal (38). Buhrer et al determined the urinary losses of Epo in preterm infants confirming that clearance from the kidney is not a major contributor to Epo elimination (123).…”
Section: Linear Clearance Pathwaymentioning
confidence: 99%
See 1 more Smart Citation